DISTRIBUSI DAN KEMELIMPAHAN TELUR NYAMUK Aedes Sp. PADA OVITRAP DAN KERENTANAN LARVA TERHADAP ABATE DI KELURAHAN WUA-WUA KOTA KENDARI - Sri aprilianti; Sernita; Muh.Sultanul Aulya; Kemal Idris (LPPM Universitas Abdurrab, 2025)
Kendari City is one of the cities with the highest cases of Dengue Hemorrhagic Fever (DHF) in Southeast Sulawesi Province. DHF is caused by infection of the Aedes Sp. mosquito whose infection spreads rapidly. Monitoring and control of vector density is carried out to see high cases of DHF. The installation of ovitraps is a way to describe the density of eggs in the area so that prevention can be carried out more effectively. In addition to the installation of ovitraps, chemical larvicide, namely temephos (abate) is used as a control of DHF vectors by sprinkling abate powder into water reservoirs. The most common vector control currently carried out is chemical control, because it is considered more effective and efficient, but if used continuously it can cause resistance in the vector. The purpose of this study was to determine the distribution and abundance of Aedes Sp. mosquito eggs in ovitraps and the susceptibility of larvae to temephos (abate). The research method used was observational by observing ovitraps, identifying larvae and calculating the percentage of larvae that successfully hatched from the ovitrap results. The results of the study showed that the number of eggs trapped in the ovitrap outside the house was 191 eggs (56.3%0 and inside the house was 148 (43.6%) Aedes Sp. The results of the Aedes Sp. larvae susceptibility test after 24 hours of exposure showed that 100% of Aedes Sp. larvae died and were classified as vulnerable. From the results of the study, it can be concluded that the abundance of Aedes sp. eggs outside the house is higher than inside the house, and the results of the susceptibility of Aedes sp. larvae are included in the vulnerable category